(untitled) (Ozone Therapy Global Journal, 2013)
The objectivewas a preliminary approach to the use of ozone in different prostatic pathologies. Prostatic diseases coexist both in middle aged and in older patients. The study was carried out right after the injection of ozone/oxygen gas, into the prostate to those patients that have been diagnosed with prostatic disease and checked with a biopsy.The initial hypothesis was that O3 protect patients against side effects as infection or bleeding, due to its scleroses and fungicide properties. The procedure, echo-directed, took place by inserting a transrectal ultrasonic probe while injecting O3 manually, using a Chiva needle23G x 178 cm. The study and a follow up involve 25 patients.The results do not show any objective benefit in cancer or Benign Prostate Hyperplasia (BPH). Nevertheless, satisfactory evolution was show in chronic prostatitis where was noticed a mitigation of symptoms during thefollow-up. The biological properties of ozone and its initial results in its applications in chronic prostatitis can be useful to extend and confirm the benefits observed in this pathology which frequently resist to conventional treatments and became a serious problem.Valuable effects in BPH or cancer remain excluded of this procedure.